Off to School: Filmic False Equivalence and Indian Residential School Scholarship - Griffith, Jane (Historical Studies in Education / Revue d'histoire de l'éducation, 2018)
This article uses two short, mid-twentieth century documentaries produced by the National Film Board of Canada as an entry point into charting popular and scholarly representations of Indian residential schools. The article begins with a close reading of one 1958 film followed by an overview of how scholarship has changed over the last fifty years, particularly alongside and sometimes because of the Truth and Reconciliation Commission of Canada. The article advocates centring survivor testimony and provides major turns in considering as well as teaching about residential schooling and settler colonialism in Canada as well as ways of how to teach about and learn from it. The article concludes with a close reading of a second film, produced in 1971 by Abenaki filmmaker Alanis Obomsawin, which offers a decidedly different perspective from the film discussed at the beginning of the article.RésuméCet article utilise deux courts documentaires produits par l’Office national du film à l’époque du centenaire de la Confédération comme point de départ permettant d’étudier les représentations populaires et universitaires des pensionnats indiens. L’article s’amorce sur une lecture attentive d’un film de 1958, puis propose un aperçu des changements survenus dans la littérature académique au cours des cinquante dernières années, en particulier grâce à la Commission de vérité et réconciliation du Canada. Il met l’accent sur le témoignage des survivants et propose des changements importants, à la fois dans la façon de comprendre le système des pensionnats et le colonialisme canadien, de même que sur les façons de l’enseigner et les leçons à en tirer. L’article se termine par l’analyse d’un second film produit en 1971par la cinéaste Abénaquis Alanis Obomsawin, qui offre une perspective très différente de celui tourné en 1958.